Uso de clean code para melhorar a qualidade do código-fonte da plataforma ativa - Vieira, Leonardo de Campos (2024)
Clean code makes the source code readable, reduces complexity and facilitates scalability, characteristics that increase the quality of a software product. Making code easier to understand lets developers increase their productivity. Literature authors present some clean code guidelines such as short methods, names of significant variables. Therefore, this work used the guidelines to improve the source code of the Ativa platform. This teaching platform was created with the intention of encouraging learning for people with intellectual disabilities through activity management and is made up of a student module and a teacher module. In the module intended for students, it is possible to play the games that were made available by the teacher. In turn, in the teacher module it is possible to register content, subjects, activities and carry out student assessment. Clean code guidelines were used in the view, model and control packages due to the lack of application of good practices when writing source code. Bugs were identified and fixed and guidelines were used such as: meaningful names, short and explanatory methods, maximize cohesion, flow analysis, clear parameters, refactoring. This allowed an improvement in code quality in accordance with clean code guidelines such as readability, complexity reduction, efficiency, resource and costs.